Promoting ER stress in a plasmacytoid dendritic cell line drives fibroblast activation - Beatriz H. Ferreira; Inês S. Silva; Andreia Mendes; Fátima Leite-Pinheiro; Adrienne W. Paton; James C. Paton; Iola F. Duarte; Philippe Pierre; Catarina R. Almeida (Cell Communication and Signaling)
Abstract Background Fibrosis remains a major complication in several chronic diseases, including systemic sclerosis (SSc). Plasmacytoid dendritic cells (pDCs) are innate immune cells that play a key role in the development of fibrosis in SSc patients, through still poorly defined mechanisms. Interestingly, endoplasmic reticulum (ER) stress signaling pathways are dysregulated in pDCs from patients with SSc, but their contribution to fibrosis remains unclear. Thus, this study aimed to unravel the mechanisms behind the involvement of pDCs and ER stress in fibrosis. Methods To address this question, we established an in vitro model designed to study the interactions between pDCs and fibroblasts. More specifically, IMR-90 fibroblasts were co-cultured with CAL-1, a pDC cell line. ER stress was then induced by the bacterial toxin SubAB. Extracellular matrix (ECM) production was assessed using immunoblotting, qPCR and confocal microscopy. The importance of cell-to-cell contact was investigated using conditioned media (CM) and transwell assays. Results Direct contact of CAL-1 and IMR-90 cells under ER stress conditions led to increased expression of fibronectin and alpha-smooth muscle actin (α-SMA). This effect required expression of the ER stress signaling sensor protein kinase R-like ER kinase (PERK) in pDCs and was observed only upon direct contact between both cell types. Conclusions Overall, our data suggest that ER stress induction in pDCs promotes fibroblast activation, which may contribute to the development of fibrosis in SSc.